Differential Item Functioning of GRE Mathematics Items Across Computerized and Paper-and-Pencil Testing Media - Gu, Lixiong; Drake, Samuel; Wolfe, Edward W. (The Journal of Technology, Learning and Assessment, 2006)
This study seeks to determine whether item features are related to observed differences in item difficulty (DIF) between computer- and paper-based test delivery media. Examinees responded to 60 quantitative items similar to those found on the GRE general test in either a computer-based or paper-based medium. Thirty-eight percent of the items were flagged for cross-medium DIF, and post hoc content analyses were performed focusing on page formatting, mathematical notation, and mathematical content of the items. Although findings suggest that differences in page formatting and response processes across the delivery media contribute little to the observed cross-medium DIF, differences in the mathematical notation contained in the item text as well as differences in the mathematical content of the items provided the strongest apparent relationships with cross-medium DIF.